Preparation and Study of Properties of Polyhydric Alcohols Biphosphate Ethanolamine Salt. Issue 1 (January 2020) - Wei, Jiang; Jinfeng, Li; Ziyuan, Li; Jie, Chen; Xiaoyan, Zhang
Abstract: A new type of halogen-free flame retardant has been synthesized with raw materials of Di(trimethylolpropane) and phosphorus oxychloride, and the influence of the raw material ratio, reaction temperature and reaction time on the yield has been discussed. It has been shown in the results that the molar ratio of Di(trimethylolpropane) and phosphorus oxychloride is 1:4, the reaction temperature is 80°C, the reaction time is 4 hours, the intermediates have the highest yield. Furthermore, the flame-retardant effect and thermal stability of the target product on different fabrics have been investigated, and the structures of the intermediates and the target products were characterized by Fourier transform infrared spectrometer.